L-DMDP, L-homoDMDP and their C-3 fluorinated derivatives: synthesis and glycosidase-inhibition. - Li, Y; Huang, M; Yamashita, Y; Kato, A; Jia, Y; Wang, W; Fleet, G; Nash, R; Yu, C (2011)
L-DMDP and L-homoDMDP, the enantiomers of naturally occurring DMDP and homoDMDP have been synthesized from D-xylose derived cyclic nitrone 9. Their 3-deoxy-3-fluorinated analogues were also obtained from polyhydroxylated fluorinated cyclic nitrone 10, which was prepared from fluorinated sugar 12 in seven steps. Bioactivities of these iminosugars against various glycosidases were evaluated. While L-DMDP and L-homoDMDP are potent inhibitors of α-glucosidases, a sharp decrease of inhibition was found when the C-3 hydroxyl group of these compounds was replaced by fluoride, which showed the great importance of the C-3 hydroxyl in their interaction with enzymes.